Effect Of Individual Vs Group Cognitive Therapy On Functional Independence In Parkinson’s Disease (International Journal of Environmental Sciences, 2025)
Introduction: Parkinson's disease (PD) is a progressive neurodegenerative disorder characterized by both motor (rigidity, tremor, gait problems) and non-motor symptoms (depression, anxiety, cognitive impairment) that have a significant impact on quality of life. While dopaminergic medications help with motor deficits, non-motor symptoms are more difficult to manage. Aaron T. Beck developed Cognitive Therapy (CT), which is an organized, time-limited treatment that addresses dysfunctional thought habits. Evidence suggests that CT lowers depressive symptoms, negative thoughts, and stress reactivity while increasing positive affect and coping. Recent trials and meta-analyses have shown that CT is useful in Parkinson's disease, improving emotional well-being, cognitive performance, and overall quality of life. Thus, CT is a significant tool in the overall care of Parkinson's disease.Objective: 1.Assess the effectiveness of Cognitive Therapy (CT) in improving cognitive function, in patients with Parkinson's disease (PD). 2.Compare the results of individual and group cognitive therapy to evaluate whether technique is more helpful in treating the cognitive symptoms of Parkinson's disease. 3.Evaluate the feasibility, accessibility, and cost-effectiveness of individual versus group cognitive therapy (CT) for controlling Parkinson's nonmotor symptoms.Methods: Thirty PD patients were divided into two groups (n=15 each). Group A received individual cognitive therapy, while Group B underwent group-based cognitive therapy for 8 weeks, 3 sessions per week. Outcome measures included Barthel Index, Montreal Cognitive Assessment (MoCA), and Parkinson’s Disease Questionnaire (PDQ-39), assessed pre- and post-intervention.Result: Both groups demonstrated significant improvement. The Barthel Index improved by 18% in Group A and 25% in Group B. MoCA scores improved by 22% in Group A and 19% in Group B. PDQ-39 scores showed 15% improvement in Group A and 28% in Group B.Conclusion: Both individual and group cognitive therapy are effective in improving functional independence in PD. However, group therapy demonstrated superior outcomes in quality of life and daily functioning, while individual therapy showed slightly better cognitive improvement. A combined approach may be most beneficial.